Building a Typology of Evaluative Competences in History, Geography and Social Sciences: Evidence from the Teaching Evaluation [Construyendo Una Tipología de Competencias Evaluativas en Historia, Geografía y Ciencias Sociales: Evidencias Desde la Evaluación Docente] - Abricot-Marchant, N (Universidad Austral de Chile, 2022)
This study analyzes the assessment practices of History, Geography and Social Sciences teachers rated as outstanding by the Chilean Teaching Evaluation System. Following a qualitative design, quantitative and qualitative inputs were combined to analyze evidence presented in the teaching portfolio. From descriptive methods, based on Grounded Theory, a set comprised of the assessment tasks and the explanations of learning outcomes was analyzed. Results provide evidence on which a typology of evaluative competencies of the teachers of the subject was built, where it is possible to relate the type of disciplinary skills requested in the assessment tasks with the characteristics of explanations about the learning outcomes of their students, demonstrating that the pedagogical content knowledge of the discipline is fundamental in the assessment processes © 2022, Estudios Pedagogicos.All Rights Reserved.